Assessment of Income Differentiation of Different-Sized Households in Poland - Laska, Karolina (Olsztyn Economic Journal, 2024)
The household is the basic economic unit that participates in both economic and social life. It must generate income, the level of which may change over time and vary depending on the size of the household. The aim of the research was to assess the scale of differentiation of household income in Poland in the years 2014-2021 due to their size. The study used the comparative analysis method. Secondary data on disposable income per person in the household was compared. The variation in income in particular years was examined using the classic coefficient of variation. In the years under study, in each type of household (taking into account its size), disposable income increased, with a higher growth rate recorded by larger households. In all years, the size of the farm significantly differentiated the level of disposable income of households, and this differentiation showed a decreasing trend.